2022
DOI: 10.1177/26350106221125695
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Cluster Randomized Controlled Trial Involving Community-Based Intervention for Older Adults With Type 2 Diabetes Mellitus in Singapore

Abstract: Purpose: The purpose of the study was to investigate the effectiveness of a community-based intervention on improving knowledge about diabetes, self-care behaviors, and glycemic control among older adults with type 2 diabetes mellitus (T2DM) in Singapore, a country in Asia with a high prevalence of diabetes. Methods: A 3-arm cluster randomized controlled trial involving community-dwelling older adults ages 55 to 99 with T2DM was conducted. Intervention group 1 and 2 participants received a 12-session intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(44 reference statements)
0
0
0
Order By: Relevance
“…Our included studies had a total sample of 5976 older adults (intervention group: n=3510; usual care group: n=2466). Each intervention arm comprised a self-management approach that fit into the five categories of Chodosh’s framework: 1 study - medical care ( 25 ); 3 studies - psychological emphasis ( 26 28 ); 4 studies – tailoring ( 29 32 ); 4 studies - group setting ( 33 36 ); and 5 studies emphasized feedback ( 37 41 ). The characteristics of the included studies may be found in Supplementary Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our included studies had a total sample of 5976 older adults (intervention group: n=3510; usual care group: n=2466). Each intervention arm comprised a self-management approach that fit into the five categories of Chodosh’s framework: 1 study - medical care ( 25 ); 3 studies - psychological emphasis ( 26 28 ); 4 studies – tailoring ( 29 32 ); 4 studies - group setting ( 33 36 ); and 5 studies emphasized feedback ( 37 41 ). The characteristics of the included studies may be found in Supplementary Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The pooled effect of diabetes self-management program interventions for older adults resulted in statistically significant improvements in the standardized mean differences in patient-reported outcomes measures for behaviour change, diabetes knowledge and self-efficacy (-0.91 SMD; 95% CI -042, 1.41; p <0.00) ( 27 , 29 , 30 , 33 , 35 38 , 40 ) ( Figure 6 ). The most effective self-management program intervention strategy associated with the greatest improvements in patient-reported outcomes was feedback (1.64; 95% CI 1.08, 2.21; p <0.01).…”
Section: Resultsmentioning
confidence: 99%